A Suicidal Adolescent: The Rocky Path from Physical Pain to Psychological Awareness. Issue 1 (1st January 2020) - Langley, Jacqueline
ABSTRACT: This article tracks detailed process material – extracted from an especially disturbing three-week period during a four-year analysis – of a suicidal adolescent. The analyst-in-training's exploration of therapeutic action to make meaningful contact with her patient is demonstrated. In particular, how her patient moves from a state of disorganization to thoughtful self-reflection and the use of concurrent work with parents are highlighted.